The Spatial Effects of Elderly Population Presence on COVID -19 Incidence In DKI Jakarta Before, During, and After Large-Scale Social Restriction - Chotib, Chotib; Raijaya, I G A A Karishma Maharani, Mrs.; Aki Muhaimin, Ahmad Aki, Mr.; Saputri, Novani (Smart City, 2021)
ABSTRACT Infected cases and suspect cases of covid-19 are increasing more and more daily. This increment happens either in whole regions of Indonesia and DKI Jakarta as a capital city. The purpose of this research is to seek the pattern in spatial of Covid-19 incidence with 3 different periods of before, during, and after large-scale social restriction, and to identify the influence of the presence of the elderly and other factors. One of the scopes of this study is the presence of the elderly because the elderly population is considered as influencing the increase of Covid-19 incidence. The analysis method used in this research is spatial analysis. Novel findings show that spatial pattern change in 3 periods of observation where clusterization of Covid-19 is more intensive, the presence of elderly is a more significant influence to the transmission of Covid-19. Also, there are spatial effects towards the influence of elderly to the spread of Covid-19. The other variables such as the number of traditional markets and population density initially insignificant turn out to be significant in the second and third period. Keywords: Covid-19, Elderly Population, Spatial Analysis, social restriction